Efektivitas Edukasi Teknik Menyusui terhadap Penyembuhan Puting Susu Lecet pada Ibu Nifas di Klinik Berkah Prima Medika - Suharti; Fetty Rosyadia Wachdin; Ririn Ratnasari (LPPM Universitas Bhamada Slawi PSDKU D III Kebidanan Kampus Kota Pekalongan, 2026)
Sore nipples are a common problem experienced by breastfeeding mothers during the postpartum period and can cause pain, discomfort, and disruption to exclusive breastfeeding. This condition is generally caused by improper breastfeeding techniques, suboptimal baby attachment, and mothers' lack of knowledge about breast care. This study aims to determine the causes and management of sore nipples in breastfeeding mothers. The research method used a descriptive approach with case studies of postpartum mothers who experienced sore nipples. Data collection was conducted through interviews, observations, physical examinations, and documentation of midwifery care. The results showed that sore nipples are influenced by improper breastfeeding positioning and attachment. Management provided included education on correct breastfeeding techniques, maintaining breast hygiene, regular breastfeeding, and recommendations for applying breast milk to the nipples after breastfeeding. After continuous midwifery care, the condition of the nipples improved and mothers were able to breastfeed more comfortably. This study is expected to provide information for health workers in improving education on breast care and correct breastfeeding techniques for postpartum mothers.